Changes in governmental leadership strategies after pandemic - Kiriukhina, Aleksandra; Farkas, Tibor (Studia Mundi – Economica, 2021)
Effective leadership is a term an understanding and underlying principles of which are a conceptually challenged and constantly evolving research topic. This article provides a brief listing of the leadership strategies used by European leaders in 2020-2021 and the tools for their implementation. The assessment the reputation consequences, which were undoubtedly influenced by the adoption of crisis decisions and the results. The author of the article will leave the question of which of the tools used in the fight against the pandemic will be implemented in the post-Covid governance agenda as a subject of reflection.